2010
DOI: 10.2353/ajpath.2010.090453
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Integrin αvβ8 Is Associated with Brain Arteriovenous Malformation Pathogenesis

Abstract: Brain arteriovenous malformations (BAVMs) are a rare but potentially devastating hemorrhagic disease. Transforming growth factor-␤ signaling is required for proper vessel development, and defective transforming growth factor-␤ superfamily signaling has been implicated in BAVM pathogenesis. We hypothesized that expression of the transforming growth factor-␤ activating integrin, ␣v␤8, is reduced in BAVMs and that decreased ␤8 expression leads to defective neoangiogenesis. We determined that ␤8 protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 43 publications
1
52
0
2
Order By: Relevance
“…Previous studies have demonstrated important roles for AP-1, p38, and TGF-␤ in normal epithelial-mesenchymal homeostasis and wound healing of the skin and lung (23,47,84,85). We have also shown that integrin ␤8 regulates epithelial-mesenchymal and endothelial-mesenchymal homeostasis in the airway and brain, respectively (1,2,15,17). Here we show a direct link between p38, AP-1, and TGF-␤ in these processes via regulation of integrin ␤8 expression.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have demonstrated important roles for AP-1, p38, and TGF-␤ in normal epithelial-mesenchymal homeostasis and wound healing of the skin and lung (23,47,84,85). We have also shown that integrin ␤8 regulates epithelial-mesenchymal and endothelial-mesenchymal homeostasis in the airway and brain, respectively (1,2,15,17). Here we show a direct link between p38, AP-1, and TGF-␤ in these processes via regulation of integrin ␤8 expression.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, a genetic variant in the ITGB8 locus has recently been found to correlate with risk of brain arteriovenous malformation development and the at-risk brain arteriovenous malformation variant was associated with reduced ␤8 protein expression (2). Here we describe the first characterization of the promoter and elements that regulate ITGB8 expression and place it under the control of p38, a stress-activated and proinflammatory protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased expression of ␣v␤8 has been found in brain arteriovenous malformations, and increased expression of ␣v␤8 has been found in airway fibroblasts from patients with fibrotic remodeling of their airway wall, one of the cardinal features of chronic obstructive pulmonary disease (COPD) (5,15,16). ITGB8 is a direct transcriptional target of IL-1␤, a crucial proinflammatory cytokine implicated in brain arteriovenous malformation and COPD pathogenesis (5,15,16).…”
mentioning
confidence: 99%
“…During brain development, ␣v␤8 integrin in neural cells promotes latent TGF␤ activation and signaling to control angiogenesis and formation of the blood-brain barrier (15)(16)(17)(18)(19)(20). Single nucleotide polymorphisms in the human ␤8 integrin (ITGB8) gene that diminish protein expression have been identified in patients with brain vascular malformations (21). ITGB8 expression levels are upregulated in nervous system malignancies, including glioblastoma (22,23) and peripheral nerve sheath tumors (24).…”
mentioning
confidence: 99%